2016
DOI: 10.1007/s00221-016-4813-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spectral audiotactile interactions in musicians

Abstract: Previous investigations have revealed that the complex sensory exposure of musical training alters audiovisual interactions. As of yet, there has been little evidence on the effects of musical training on audiotactile interactions at a behavioural level. Here, we tested audiotactile interaction in musicians using the audiotactile illusory flash and the parchment-skin illusion. Significant differences were only found between musicians and non-musicians for the audiotactile illusory flash. Both groups had simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, compared to non-musicians, trumpet players display significantly increased cortical signal strength for combined auditory-somatosensory stimuli exclusively for tactile stimulation of their lips ( Schulz et al, 2003 ). Musicians have also been found to react faster to tactile and non-musical auditory stimuli presented either separately or together ( Landry and Champoux, 2017 ), are less affected by the audio-tactile flash illusion—where presentation of one tactile stimulus with multiple task-irrelevant tones normally leads to the perception of more than one touch ( Landry et al, 2017 ), and are more sensitive to audio-tactile incongruencies than non-musicians ( Kuchenbuch et al, 2014 ). In fact, musical training also appears to narrow the temporal integration window for binding auditory and visual signals ( Petrini et al, 2009 ), which is seen for music, but not speech ( Lee and Noppeney, 2011 ).…”
Section: Interactions Between Auditory and Somatosensory Inputs In Th...mentioning
confidence: 99%
“…For example, compared to non-musicians, trumpet players display significantly increased cortical signal strength for combined auditory-somatosensory stimuli exclusively for tactile stimulation of their lips ( Schulz et al, 2003 ). Musicians have also been found to react faster to tactile and non-musical auditory stimuli presented either separately or together ( Landry and Champoux, 2017 ), are less affected by the audio-tactile flash illusion—where presentation of one tactile stimulus with multiple task-irrelevant tones normally leads to the perception of more than one touch ( Landry et al, 2017 ), and are more sensitive to audio-tactile incongruencies than non-musicians ( Kuchenbuch et al, 2014 ). In fact, musical training also appears to narrow the temporal integration window for binding auditory and visual signals ( Petrini et al, 2009 ), which is seen for music, but not speech ( Lee and Noppeney, 2011 ).…”
Section: Interactions Between Auditory and Somatosensory Inputs In Th...mentioning
confidence: 99%
“…Lu et al also found, using magnetoencephalography (MEG), that musicians exhibited greater neural activity in various temporal regions of the brain in response to synchronous stimuli, and greater activity in the cerebellum in response to asynchronous stimuli. Later studies found that musicians demonstrate greater multisensory integration as measured by audiotactile reaction times 24 , and are less susceptible to the sound-induced flash illusion 25 and its audiotactile equivalent 26 .…”
Section: Introductionmentioning
confidence: 99%
“…At the behavioral level, it has been shown that in detections tasks, musicians react faster to auditory and tactile stimuli (Landry and Champoux, 2017) and are also better at integrating auditory and tactile information (Landry et al, 2017). In auditory frequency discrimination tasks, musicians have lower threshold compared to controls (Spiegel and Watson, 1984), and this effect appears to be correlated with years of musical expertise (Kishon-Rabin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%